Penguatan Profitabilitas UMKM Camilan Tradisional Melalui Inovasi Cita Rasa dan Tata Kelola Usaha Sederhana - Sofyan Hakim; Dian Ana Mutriqah; Hilmi Satria Himawan; Karina Awalia Zahra; Irdayani Sagita Anindi; Nurlusiana Nurlusiana; Ade Widya Rahmah (Pusat Riset dan Inovasi Nasional, 2026)
Traditional snack micro, small, and medium enterprises (MSMEs) in Indonesia face increasing market competition and rapidly changing consumer preferences, particularly among younger consumers seeking innovative and symbolic food experiences. This community engagement study aims to strengthen the profitability and sustainability of traditional snack MSMEs by integrating local flavor innovation with simple business governance practices. Using a participatory action research approach under the Merdeka Belajar Kampus Merdeka (MBKM) program in Palangka Raya, this study involved co-creation between students and local entrepreneurs in product development, production standardization, and basic financial management. Qualitative data were collected through participatory observation and stakeholder discussions, while quantitative data were obtained from sales records and simple financial reports. The results demonstrate that local flavor-based innovation, combined with standardized operating procedures and cost control mechanisms, improved product differentiation, operational efficiency, and financial performance. The intervention generated a positive net profit and strengthened the partner’s capacity for independent business management. This study contributes to the literature by positioning traditional food MSMEs as sites of cultural innovation and micro-governance, while supporting Sustainable Development Goals related to inclusive economic growth, cultural preservation, and responsible production.